Effect of investment, GRDP percapita, and original local government revenue on regional financial independence through capital expenditure as intervening variables - Yusiawati, Diana; Marhaeni, A.A.I.N. (International research journal of management, IT and social sciences, 2020)
This study aims to see the significance of investment, GDRP per capita, Original Local Government Revenue on regional finance independence. This population in this study were districts/cities in Bali Province from 2014 to 2018. This study used a sample with the census method. The data analysis technique used is path analysis. These results showed that investment has a positive and insignificant effect on capital expenditure and has a positive and significant effect on regional finance independence, GRDP per capita has a significant negative effect on capital expenditure and has a significant positive effect on regional financial independence, Original Local Government Revenue (PAD) has a significant positive effect on regional financial independence while the positive and insignificant effect of capital expenditure on regional financial independence.